ANALISIS GAYA BELAJAR SERTA PENGARUH TERHADAP HASIL BELAJAR MATEMATIKA SISWA SELAMA PANDEMI COVID-19 - Kristin Pardede; Marzuki Ahmad; Muhammad Syahril Harahap (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2021)
This study aims to find out the learning style of students an the relationship of students learning style to the results of students' mathematics learning in the V neighborhood, losung village during the covid-19 pandemic. There are three types of learning styles that will be discussed in this study, namely auditorial visual and kinesthetic. The method used is qualitative method. Closed questionnaire, unstructured interviews, and documentation are used in data collection. Miles and Huberman tecniques are used in data collection, include 1) data reduction, 2) data presentation, and 3) data verification. The result showed that junior high school students in environment V in mathematics learning dominantly have a visual learning style with a total of 5 people (50%) with an average rating of 77.6. Auditorial learning style with a total of people (20%) with an average score of 70, while kinesthetic learning style with a total of peopl (30%) with an averag rating of 56.6. During the covid-19 pandemic students with visual learning styles learn better than students with auditorial and kinesthetic learning styles.